Treatment of aneurysmal bone cysts using endoscopic curettage - Aiba, Hisaki (BMC Musculoskelet Disord, 2018)
BACKGROUND: Although aneurysmal bone cysts (ABCs) are benign tumours, they have the potential to be locally aggressive. Various treatment approaches, such as en bloc resection, open curettage, radiotherapy, sclerotherapy, and embolization have been proposed, but the most appropriate treatment should be selected after considering the risk of tumour recurrence and treatment complications. Endoscopic curettage (ESC) may be a less invasive alternative to open curettage for ABC treatment. We aimed to describe the use of ESC for the treatment of ABCs and to report our clinical outcomes, including the incidence rate of recurrence, radiological appearance at final follow-up, time to solid union, complications, and postoperative function. METHODS: Between 1998 and 2015, 30 patients (18 men and 12 women; mean age, 17.4 years) underwent ESC for the treatment of primary ABCs at our hospital (mean postoperative follow-up, 55 months). ESC was performed under arthroscopic guidance for direct visualization, and curettage extended until normal bone was observed in the medullary cavity. To investigate bone healing after ESC, we evaluated the consolidation of cysts at the final evaluation (based on the modified Neer classification) and time to solid union after surgery, which was defined as sufficient cortical bone thickness to prevent fracture and allow physical activities. RESULTS: Recurrence was identified in 3 cases (10%). Curative outcomes were obtained after repeated ESC or open curettage. A log-rank analysis indicated that age < 10 years (p = 0.004) and contact of the tumour with the physis (p = 0.01) increased the risk of tumour recurrence. Residual tumours were identified in 9 cases (30%); these lesions remained inactive over the extended follow-up period. The average time to solid union after endoscopic curettage was 3.2 months. Transient radial nerve palsy was identified in 1 case. Good postoperative functional recovery occurred in all cases. CONCLUSIONS: ESC is a minimally invasive technique for the treatment of ABCs, and the tumour recurrence rate is comparable to that of other standard procedures. However, the application of this method should be carefully considered, especially for patients < 10 years and when the tumour comes in contact with the physis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12891-018-2176-6) contains supplementary material, which is available to authorized users.